Evidence for Innate and Adaptive Immune Responses in a Cohort of Intractable Pediatric Epilepsy Surgery Patients - Owens, Geoffrey C.; Garcia, Alejandro J.; Mochizuki, Aaron Y.; Chang, Julia W.; Reyes, Samuel D.; Salamon, Noriko; Prins, Robert M.; Mathern, Gary W.; Fallah, Aria (Frontiers in Immunology, 2019)
Brain-infiltrating lymphocytes (BILs) were isolated from resected brain tissue from ten pediatric epilepsy patients who had undergone surgery for Hemimegalencephaly (HME) (n=1), Tuberous sclerosis complex (TSC) (n=2), Focal cortical dysplasia (FCD) (n=4), and Rasmussen encephalitis (RE) (n=3). Peripheral blood mononuclear cells (PBMCs) were also isolated from blood collected at the time of the surgery. Cells were immunostained with a panel of 20 antibody markers, and analyzed by mass cytometry. To identify and quantify the immune cell types in the samples, an unbiased clustering method was applied to the entire data set. More than 85 percent of the CD45+ cells isolated from RE brain tissue comprised T cells; by contrast NK cells and myeloid cells constituted 80-95 percent of the CD45+ cells isolated from the TSC and the FCD brain specimens. Three populations of myeloid cells made up >50 percent of all of the myeloid cells in all of the samples of which a population of HLA-DR+ CD11b+ CD4- cells comprised the vast majority of myeloid cells in the BIL fractions from the FCD and TSC cases. CD45RA+ HLA-DR- CD11b+ CD16+ NK cells constituted the major population of NK cells in the blood from all of the cases. This subset also comprised the majority of NK cells in BILs from the RE and HME brain tissue, whereas NK cells defined as CD45RA- HLA-DR+ CD11b- CD16- cells comprised 86-96 percent of the NK cells isolated from the FCD and TSC brain tissue. Thirteen different subsets of CD4 and CD8 alpha beta T cells and gamma delta T cells accounted for over 80% of the CD3+ T cells in all of the BIL and PBMC samples. At least 90 percent of the T cells in the RE BILs, 80 percent of the T cells in the HME BILs and 40-66 percent in the TSC and FCD BILs comprised activated antigen-experienced (CD45RO+ HLA-DR+ CD69+) T cells. We conclude that even in cases where there is no evidence for an infection or an immune disorder, activated peripheral immune cells may be present in epileptogenic areas of the brain, possibly in response to seizure-driven brain inflammation.